Interprofessional learning enhances knowledge of roles but is less able to shift attitudes: a case study from dental education - Evans, J. L.; Henderson, A.; Johnson, N. W. (European journal of dental education, 2012)
Introduction:  Interprofessional education (IPE) purports to improve team working through improved knowledge of the roles of others, and by engendering mutual respect. This case study aimed to determine the impact of an IPE curriculum on knowledge and attitudes of dentistry and dental technology students undertaking these curricula in the new School of Dentistry and Oral Health at Griffith University. All dental technology students and third‐ and final‐ (fifth) year dentistry students were invited to participate. Method:  A mixed‐method approach was used to compare attitudes, perceptions and experiences of students involved in our IPE curricula. Quantitative data were evaluated with the Statistical Package for the Social Sciences (SPSS), and qualitative findings were explored through an Excel® spreadsheet coding frame tested against LeximancerTM qualitative software for consistency. Results:  Forty‐six of the 131 eligible students participated. Readiness for Interprofessional Learning Scales (RIPLS) and focus groups consistently showed that IPE positively influenced professional identity and improved communication between and amongst all students and assisted them in developing their roles. A prevailing sense of greater importance and a lack of mutual respect between dentistry and dental technology students were, unfortunately, evident. The process was, however, sufficient to enhance teamwork and collaboration when planned learning revolved around explicit patient care in the provision of dental prostheses. Conclusion:  Further development of such curricula is needed to maximise IP learning (IPL) opportunities, to shift traditional attitudes and, potentially, to improve the outcomes of patient care. To enable this, academic and clinical leaders need to embrace the ideals of IPE.